Change in time preferences: Evidence from the Great East Japan Earthquake - Mika Akesaka (Osaka University, Institute of Social and Economic Research (ISER), 2018)
This study examines whether individuals' time preferences are affected by the damage resulting from the tsunami in the Great East Japan Earthquake of 2011, using panel surveys before and after the earthquake. When the change in time preferences is measured using the (â, ä) model, I find that the present bias tendency is increased (shrinking â), although the change in the time discount rate (ä) is not statistically significant for those affected by the tsunami. This study also investigates changes in time preferences using other behavioral indicators. The results show that those affected by the tsunami are more prone to impulse shopping, procrastination, unplanned overconsumption, and increased body mass indices (BMI). Moreover, I find gender heterogeneous changes in time preferences. Changes in time preferences appeared in males immediately after the earthquake in 2012 and 2013, and have been subsiding thereafter. On the other hand, these changes appeared in females in 2016 and 2017, i.e., after a lag since the earthquake.
Keywords: C23; D91; Q54; 330; Natural disasters; Preference stability; Time preference; Present bias